Odpowiedzi

Najlepsza Odpowiedź!
2010-04-12T15:37:14+02:00
A) 4c-(3c+2)-10c=4c-3c-2-10=c-12
b)-5(3y-7)-2(6+4y)+3y=-15y+35-12-8y=-23y+23

a) 5a+4(a-1)=5a+4a-4=9a-4
b)3x-0,2(1-2x)=3x-0,2+0,4x=3,4x-0,2
2010-04-12T15:37:25+02:00
A) 4c-(3c+2)-10c=4c-3c-2-10c=-9c-2
b)-5(3y-7)-2(6+4y)+3y=-15y-35-12-8y+3y=-20y-47

a) 5a+4(a-1)=5a+4a-4=9a-4
b)3x-0,2(1-2x) =3x-0,2+0,4x=3,4x-0,2


pozdr
1 5 1
2010-04-12T15:38:05+02:00
1.Usuń nawiasy i wykonaj redukcję wyrazów podobnych.
a) 4c-(3c+2)-10c=4c-3c-2-10c=-9c-2
b)-5(3y-7)-2(6+4y)+3y=15y+35-12-8y+3y=10y+23
2.Wykonaj mnożenie i redukcję wyrazów podobnych.
a) 5a+4(a-1)=5a+4a-4=9a-4
b)3x-0,2(1-2x) =3x-0,2+0,4x=3,4x-0,2